Sinergi Antartingkatan Pemerintahan dalam Penghapusan Kemiskinan di Kabupaten Kepulauan Meranti - budiman, fajar (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2025)
Kepulauan Meranti Regency occupies a strategic position in the IMS-GT growth triangle; however, it records the highest poverty rate in Riau Province (23.15% in 2024) and ranks 45th nationally. This study aims to analyze the alignment of local poverty alleviation policies with provincial and national policies. The approach utilizes comparative policy analysis of the RPJMN 2025–2029, Riau Province RPJMD 2025–2029, and Kepulauan Meranti Regency RPJMD 2025–2029 documents, as well as USG (Urgency, Seriousness, Growth) analysis to identify root causes. The findings reveal that the low quality of human development is the primary root cause of poverty. The study found that the synergy of poverty eradication programs within the Draft RPJMD of Kepulauan Meranti Regency is not optimally aligned with higher-level government policy directions. Additionally, fiscal allocation inefficiency was identified, where 32.23% of the budget is absorbed by poverty-related programs without effectively reducing poverty rates. This study concludes by recommending the establishment of a formal